Concerns and Help-Seeking Among Patients Using Opioids for Management of Chronic Noncancer Pain. Issue 4 (11th May 2018) - Larance, Briony; Campbell, Gabrielle; Moore, Teleri; Nielsen, Suzanne; Bruno, Raimondo; Lintzeris, Nicholas; Cohen, Milton; Hall, Wayne; Mattick, Richard; O'Donnell, Courtney; Degenhardt, Louisa
Abstract: Background: The safety and efficacy of long-term opioid treatment for chronic noncancer pain (CNCP) remains controversial. This study examined whether patients who report problematic opioid use sought help and/or perceived barriers to help-seeking. Methods: Data were collected from 1, 086 people prescribed opioids for CNCP via a large prospective cohort called the Pain and Opioids IN Treatment (POINT) study. Patients' characteristics and help-seeking were examined according to scores on the Prescribed Opioids Difficulties Scale (PODS). Results: Participants scoring "intermediate" (17%) or "high" (30%) on the PODS were younger and reported more complex pain presentations, higher opioid doses, poorer physical health, moderate to severe anxiety and depression, aberrant behavior, past month opioid use disorder and help-seeking (compared with the "low" PODS group, 53%). One-quarter (26%) had sought help, most commonly from a primary care physician, specialist pain clinic, family member/partner, counselor/psychologist, and the Internet. Participants in the "high" PODS group were more likely to have sought help from an alcohol or other drug service, addiction specialist, or drug information helpline. Common barriers to help-seeking were desire for self-management and concern that their opioid treatment may be discontinued. Although 35% met criteria for likely opioid use disorder, only 4.8% reported lifetime treatment with methadone or buprenorphine; participants' ratings indicated significant perceived stigma associated with these medications. Conclusions: The PODS is effective in identifying patients who are concerned about their opioid use. Strategies to address stigma related to drug treatment, including better integration of primary health, specialist pain, and addiction services, are important in reducing opioid-related harm.